The Variation and Correlation of Serum Adiponectin, Nesfatin-1, IL-6, and TNF-α Levels in Prediabetes - Huang, Kangkang; Liang, Yunlai; Ma, Yating; Wu, Jiahui; Luo, Huidan; Yi, Bin (Frontiers in Endocrinology, 2022)
Background The variation and correlation among adiponectin, nesfatin-1, tumor necrosis factor α (TNF-α), and interleukin 6 (IL-6), which may be involved in the development of the decline of health into prediabetes and diabetes, have not been elucidated. This study aims to investigate the roles of these cytokines in this process. Methods Seventy-two type 2 diabetes mellitus (T2DM) patients, 75 prediabetics, and 72 healthy individuals were enrolled in our case control study. Serum adiponectin, nesfatin-1, TNF-α, and IL-6 were tested with appropriate kits, and primary data were analyzed with correct methods. Results Serum levels of each cytokine in patients with prediabetes were between T2DM and the healthy, and significant differences were found among them. TNF-α and nesfatin-1 levels in T2DM were obviously different compared to prediabetes or the healthy; IL-6 and adiponectin levels in the healthy group were significantly changed in contrast to prediabetes or T2DM. Correlation analysis found that in prediabetics, adiponectin was positively correlated with TNF-α (R = 0.2939, P = 0.0105) and IL-6 (R = 0.3918, P = 0.0005), and their relationship was greatly strengthened in prediabetes accompanied by insulin resistance (TNF-α: R = 0.7732, P < 0.0001, IL-6: R = 0.6663, P = 0.0005). We also demonstrated that declined adiponectin (OR = 6.238, P = 0.019) and nesfatin-1 (OR = 2.812, P = 0.01) and elevated TNF-α (OR = 5.541, P = 0.001) were risk factors for prediabetes toward diabetes. Conclusions This research proved significant variations of adiponectin, nesfatin-1, IL-6, and TNF-α levels in the healthy, prediabetics, and T2DM, suggesting a slow and gradual change during the progression from a healthy condition toward diabetes via prediabetes.